Herbo-mineral formulation, Divya-Swasari-Vati averts SARS-CoV-2 pseudovirus entry into human alveolar epithelial cells by interfering with spike protein-ACE 2 interaction and IL-6/TNF-α /NF-κB signaling - Balkrishna, Acharya; Goswami, Sudeep; Singh, Hoshiyar; Gohel, Vivek; Dev, Rishabh; Haldar, Swati; Varshney, Anurag (Frontiers in Pharmacology, 2022)
The herbo-mineral formulation, Divya-Swasari-Vati (DSV), is a well-known Ayurvedic medication for respiratory ailments. In a recent pre-clinical study conducted, DSV rescued humanized zebrafish from SARS-CoV-2 S-protein-induced pathologies. This merited for an independent evaluation of DSV as a SARS-CoV-2 entry inhibitor in the human host cell and its effectiveness in ameliorating associated cytokine production. The ELISA-based protein-protein interaction study showed that DSV inhibited the interactions of recombinant human ACE 2 with three different variants of S proteins, namely, Smut 1 (the first reported variant), Smut 2 (W436R variant) and Smut 3 (D614G variant). Entry of recombinant vesicular stomatitis SARS-CoV-2 (VSVppSARS-2S) pseudovirus, having firefly luciferase and EGFP reporters, was assessed through luciferase assay and fluorescent microscopy. DSV exhibited dose-dependent inhibition on VSVppSARS-2S pseudovirus entry into human lung epithelial A549 cells and also suppressed elevated levels of secreted pro-inflammatory cytokines such as interleukin-6 (IL-6), interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α) induced by viral infection mimicking Poly I:C-, S-protein- and VSVppSARS-2S pseudovirus. In human immune cells, DSV also moderated TNF--mediated NF-B induction, in a dose-dependent manner. The observed anti-viral effect of DSV against SARS-CoV-2 is attributable to the presence of different metabolites Summarily, the observations from this study biochemically demonstrated that DSV interfered with the interaction between SARS-CoV-2 S-protein and human ACE 2 receptor which consequently, inhibited viral entry into the host cells and concomitant induction of inflammatory response.